PEMILIHAN MODA TRANSPORTASI MENUJU KAMPUS MAHASISWA UNIVERSITAS MUSLIM INDONESIA - Rani Bastari Alkam; Lambang Basri Said (Jurnal Transportasi, 2018)
Abstract One aspect that can be reviewed in transportation demands and services is the choice of transportation modes. This study aims to analyze the characteristics of the choice of transportation modes to campus by students of the Moslem University of Indonesia. Data collection was carried out by distributing questionnaires to the students of Moslem University of Indonesia as respondents, who were chosen by cluster random sampling method, with proportional amounts based on each faculty. Data were analyzed by conducting descriptive statistical tests based on survey data with questionnaire instruments. The results of the analysis in this study show that the highest proportion of mode selected is 70.34% for private transportation, 13.81% for public transportation, 11% for application-based transportation and motorized rickshaw, and the rest, 4.86%, are respondents who choose to walk to campus. Descriptively, respondents chose travel time as the most influencing factor in choosing transportation mode, which is 29.92%, followed by travel costs and convenience of 24.04% and 13.81%, respectively. Keywords: mode choice, transportation, private transportation, public transportation  Abstrak Salah satu aspek yang dapat ditinjau dalam kebutuhan dan pelayanan transportasi adalah pemilihan moda transportasi. Penelitian ini bertujuan untuk menganalisis karakteristik pemilihan moda transportasi menuju kampus oleh mahasiswa Universitas Muslim Indonesia. Pengumpulan data dilakukan dengan penyebaran kuesioner kepada mahasiswa Universitas Muslim Indonesia sebagai responden yang dipilih menggunakan metode cluster random sampling dengan jumlah yang proporsional di setiap fakultas. Data dianalisis dengan melakukan uji statistika deskriptif berdasarkan data hasil survei dengan instrumen kuesioner. Hasil analisis pada penelitian ini menunjukkan urutan proporsi penggunaan moda terbanyak adalah angkutan pribadi 70,34%, angkutan umum 13,81%, angkutan berbasis aplikasi dan becak motor 11%, dan sisanya adalah responden yang memilih untuk berjalan kaki menuju kampus (4,86%). Secara deskriptif, responden memilih waktu tempuh sebagai faktor yang paling memengaruhinya dalam memilih moda transportasi, yaitu (29,92%), disusul biaya tempuh dan kemudahan berturut-turut sebesar 24,04% dan 13,81%. Kata-kata kunci: pemilihan moda, transportasi, angkutan pribadi, angkutan umum